Clarendon News - January 12, 1883 - (:unkn) unknown (My University, 1883)
Microfilm provided by the Panhandle-Plains Historical Museum and Clarendon ISD.
A monthly newspaper in Clarendon, TX dedicated to the news of development and settlement in the northwest.
Issued twice a month. 4 pages
Volume 5, Number 28
Keywords: Clarendon News; Clarendon (Tex.)--Newspapers.; Donley County (Tex.)--Newspapers.